Comparison of the technological background of aquaponic systems - Homoki, Dávid; Minya, Dániel; Kovács, László; Molnár, Áron; Balogh, Katalin; Bársony, Péter; Fehér, Milán; Kövics, György; Stündl, László (Acta Agraria Debreceniensis, 2020)
Aquaponics is the combined culture of fish and plants in recirculating aquaculture systems, an ecologically sustainable horticultural production technique with long traditions.The objective of this study is to compare flood-and- drain, and the water crossflow system and examine the differences in the water quality, fish yield and plant growth parameters for Common carp (Cyprinus carpio) and basil (Ocimum basilicum). During the study, water quality parameters of two treatments were compared in temperatures, pH, EC and NO3¯N were significantly different (p